Caffeine as an opioid analgesic adjuvant in fibromyalgia - Scott, J Ryan (J Pain Res, 2017)
BACKGROUND: Caffeine’s properties as an analgesic adjuvant with nonsteroidal anti-inflammatory drugs/acetaminophen are well documented. However, little clinical research has explored caffeine’s effects on opioid analgesia. This study assessed the effects of caffeine consumption on pain and other symptoms in opioid-using and nonusing chronic pain patients meeting the survey criteria for fibromyalgia. MATERIALS AND METHODS: Patients presenting to a university-based pain clinic completed validated self-report questionnaires assessing symptoms. Patients (N=962) meeting the fibromyalgia survey criteria were stratified by opioid use and further split into groups based on caffeine amount consumed per day (no caffeine, or low, moderate, high caffeine). Analysis of covariance with Dunnett’s post hoc testing compared pain and symptom severity between the no caffeine group and the caffeine consuming groups. RESULTS: In opioid users, caffeine consumption had modest but significant effects on pain, catastrophizing, and physical function. Lower levels of pain interference were associated with low and moderate caffeine use compared to no caffeine intake. Lower pain catastrophizing and higher physical function were observed in all caffeine dose groups, relative to the no caffeine group. Lower pain severity and depression were observed only in the moderate caffeine group. In opioid nonusers, low caffeine intake was associated with higher physical function; however, no other significant effects were observed. CONCLUSION: Caffeine consumption was associated with decreased pain and symptom severity in opioid users, but not in opioid nonusers, indicating caffeine may act as an opioid adjuvant in fibromyalgia-like chronic pain patients. These data suggest that caffeine consumption concomitant with opioid analgesics could provide therapeutic benefits not seen with opioids or caffeine alone.